Comparison of optimization-modelling methods for metabolites production in escherichia coli - Lee, M. K.; Mohd Saberi, Mohamad; Choon, Yee Wen; Kauthar, Mohd Daud; Nurul Athirah, Nasarudin; Mohd Arfian, Ismail; Zuwairie, Ibrahim; Suhaimi, Napis; Sinnott, Richard O. (De Gruyter, 2020)
The metabolic network is the reconstruction of the metabolic pathway of an organism that is used to represent the interaction between enzymes and metabolites in genome level. Meanwhile, metabolic engineering is a process that modifies the metabolic network of a cell to increase the production of metabolites. However, the metabolic networks are too complex that cause problem in identifying near-optimal knockout genes/reactions for maximizing the metabolite’s production. Therefore, through constraint-based modelling, various metaheuristic algorithms have been improvised to optimize the desired phenotypes. In this paper, PSOMOMA was compared with CSMOMA and ABCMOMA for maximizing the production of succinic acid in E. coli. Furthermore, the results obtained from PSOMOMA were validated with results from the wet lab experiment.